COMPARATIVE STUDY OF FSH, LH, PROLACTIN, AND TSH INCASES OF PRIMARY INFERTILITY, CASES OF EARLY PREGNANCY LOSS, AND NORMAL FERTILE WOMEN - SEEMA; KAUR, MANINDER; MOHI, MANJIT KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This study aimed to assess and compare follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, and thyroid-stimulating hormone (TSH) levels in normal fertile females, patients with primary infertility, and patients with early pregnancy loss (EPL). Methods: Patients were divided into three groups of 25 each. Group I consisted of patients of primary infertility, Group II consisted of patients of EPL, and Group C consisted of normal fertile females and acted as the control group. Hormone levels in different groups were compared statistically. Results: FSH levels in the infertility group (Group I) and control group (Group C) were similar (p>0.05). The difference between the FSH levels of EPL (Group II) and the control group (Group C) was statistically significant (p<0.05). There was a statistically significant difference between LH levels of the infertility group (Group I), EPL (Group II), and control group (Group C) (p<0.05). The difference between prolactin levels of the infertility group (Group I), EPL (Group II), and control group (Group C) was also statistically significant (p<0.05). The difference between the TSH levels of the infertility group (Group I), EPL (Group II), and control group (Group C) was also statistically significant (p<0.05). Conclusion: This study supports the fact that women with infertility and repeated abortions have altered hypothalamic–pituitary–ovarian axis as compared to fertile women.